2010
DOI: 10.1128/jvi.02306-09
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of an Inherent Membrane Targeting Signal Is Responsible for the Failure of the Matrix (M1) Protein of Influenza A Virus To Bud into Virus-Like Particles

Abstract: The matrix protein (M1) of influenza A virus is generally viewed as a key orchestrator in the release of influenza virions from the plasma membrane during infection. In contrast to this model, recent studies have indicated that influenza virus requires expression of the envelope proteins for budding of intracellular M1 into virus particles. Here we explored the mechanisms that control M1 budding. Similarly to previous studies, we found that M1 by itself fails to form virus-like-particles (VLPs). We further dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
90
1
2

Year Published

2010
2010
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 70 publications
(117 reference statements)
8
90
1
2
Order By: Relevance
“…1b); however, the amount of M1 released with the budding VLPs in the supernatant was approximately half that found in virus-infected cells. This is compatible with previous reports that M1 requires interaction with other viral proteins, such as the structural proteins HA/NA (Wang et al, 2010), as well as with vRNPs, which are absent from VLPs. Using TEM, the VLPs were seen to be pleomorphic, with spherical or filamentous forms (Fig.…”
Section: Determination Of Minimal Virus Requirements For Vlp Formatiosupporting
confidence: 93%
See 1 more Smart Citation
“…1b); however, the amount of M1 released with the budding VLPs in the supernatant was approximately half that found in virus-infected cells. This is compatible with previous reports that M1 requires interaction with other viral proteins, such as the structural proteins HA/NA (Wang et al, 2010), as well as with vRNPs, which are absent from VLPs. Using TEM, the VLPs were seen to be pleomorphic, with spherical or filamentous forms (Fig.…”
Section: Determination Of Minimal Virus Requirements For Vlp Formatiosupporting
confidence: 93%
“…Gó mezPuertas et al (2000) suggested that M1 plays the major role in driving virus budding from the cellular membrane, whereas Chen et al (2007) found that M1 was not essential for the process, but that HA and NA were necessary. A recent publication (Wang et al, 2010) confirmed that M1 by itself fails to form VLPs, probably due to a lack of membrane-targeting signal, and therefore requires interaction with other viral proteins to be incorporated into the budding virions. In our study, although small amounts of M1 were released from cells expressing M1 alone, no budding particles were observed by TEM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…M2 protein associates mainly with the periphery of lipid rafts and is largely excluded from virions. In contrast, M1 cannot target the plasma membrane in the absence of other viral proteins (10,11). M1 expressed alone in cells cannot form virus-like particles (12) and likely targets the plasma membrane by associating with the cytoplasmic tails of the viral transmembrane proteins such as HA, NA (13,14), and M2 (11,15).…”
mentioning
confidence: 99%
“…Early studies using various expression systems showed that M1 alone could form virus-like particles (VLPs) (12,21). In contrast, recent work by Chen et al (7) and Wang et al (47) suggests that M1 cannot form VLPs by itself and that other viral proteins are required. Wang et al also showed that M1 does not have an inherent membrane targeting signal and is trafficked to the plasma membrane with the help of M2.…”
mentioning
confidence: 99%
“…Wang et al also showed that M1 does not have an inherent membrane targeting signal and is trafficked to the plasma membrane with the help of M2. M1 and M2 can form VLPs together in the absence of any other viral proteins (47). Thus, M1 is an integral part of the infectious virion and plays an important role in virus assembly and budding.…”
mentioning
confidence: 99%